CHARACTERISTICS OF THE FORMATION'S PEDAGOGICAL SYSTEM TO THE FUTURE SPECIALIST'S SOCIAL COMPETENCE IN THE PROFESSIONAL SOCIONOMIC SPECIALTIE'S TRAINING - Tyulpa, T.M (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article specify that social competence is a socio-pedagogical category that denotes a polyphonic personal education that allows an individual to active interact with society, establish contacts with various groups and individuals, as well as participate in socially significant projects and productively perform various social roles, which must be formed systematically. The system as a structural and functional relationship of parts of the whole, its elements, based on the complex interaction of internal and intersystem relations, allows to consider the process of formation of social competence of future specialists in socionomic specialties, to determine the structure, relationships between elements within the system and environment; to determine the principles of functioning of the system of formation of the specified quality in pedagogical activity in the conditions of sociocultural environment of institutions of higher education, is provided with the corresponding maintenance, character of interaction of subjects of educational space, adequacy of pedagogical, methodical and didactic means. It is proved that social competence is an element of the metasystem of professional competence; its formation is a part of the professional specialists training process; higher professional education as an environment in which the process of formation of social competence takes place is a subsystem of higher professional education, which in turn is a component of education in general. The properties of the system of future specialists social competence formation of socionomic specialties are distinguished: structure, integrativeness, openness, heterogeneity, hierarchy. The main features of the pedagogical system are predicted: dynamism, uniqueness and, at the same time, the presence of extreme opportunities; flexibility, stability, variability, purposefulness. The specific functions of the system are determined: translations of social experience, regulatory, epistemological, socio-educational, ideological, adaptive, axiological. The structure of the pedagogical system formation of social competence for intended socionomic specialists is presented, which contains the purpose, tasks, content-procedural, organizational-methodical aspects, the prospective outcomes.